2017
DOI: 10.1371/journal.pone.0172216
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured versus self-reported physical activity in children and adolescents with cancer

Abstract: ObjectiveExisting research recognizes low levels of physical activity in pediatric patients with cancer, but much uncertainty exists about their capability to self-reflect physical activity levels. The objective of this study was to compare results of subjective self-reports and objective accelerometers regarding levels of daily walking as well as moderate-to-vigorous physical activities.MethodsResults of the objective assessment tool StepWatchTM Activity Monitor and self-reporting with a standardized question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…Other outcome measures gaining a negative moderate rating were the ASKp and the KiGGS‐AQ. The ASKp displayed ceiling effects and the KIGGS‐AQ did not correlate with objectively measured activity levels . This limitation of the KIGGS‐AQ is in line with literature reporting that children tend to overestimate their moderate‐to‐vigorous physical activity, a limitation worth considering given the prevalence of inactivity in paediatric cancer populations .…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Other outcome measures gaining a negative moderate rating were the ASKp and the KiGGS‐AQ. The ASKp displayed ceiling effects and the KIGGS‐AQ did not correlate with objectively measured activity levels . This limitation of the KIGGS‐AQ is in line with literature reporting that children tend to overestimate their moderate‐to‐vigorous physical activity, a limitation worth considering given the prevalence of inactivity in paediatric cancer populations .…”
Section: Discussionsupporting
confidence: 67%
“…Nine hundred articles were excluded based on title and abstract with substantial agreement between reviewers ( K = 0.63, 95% CI 0.47–0.79). Thirty‐seven articles were sourced in full text, of which 21 were excluded leaving 16 articles (see Figure ) that assessed the measurement properties of 12 outcome measures (see Table ). Content and construct validity were most commonly assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that young patients with cancer have problems to reliably self-reflect levels of physical activity. 16 While a relevant number of patients overestimated their daily minutes of walking, underestimation occurred same as often. Lacking self-reflection of physical activity levels seems to be an important issue for children during cancer treatment.…”
Section: Introductionmentioning
confidence: 95%